Analisis Efektivitas Komunikasi Organisasi dalam Penerapan Sistem Informasi Manajemen Akademik - Dhiny Dhiny; Muhammad Syamsun; Ivanovich Agusta (Institut Pertanian Bogor, 2017)
Management Information System required at Departement of Sains Communication and Community Development is able to answer the needs of academic problems. The application of information technology for organizations, would be beneficial if the application in accordance with the purpose, vision and mission of the organization. which has been translated into communication efectiveness. With the qualitative method, this study provide which part of internal communication were lack and unefective. The use of information technology systems will be needed to support the success of the organization's objectives in the field of education in the future, the strategic planning technology development information and communication technologies (ICTs) can be used as a guide to improve the performance and competitive value of Departement of Sains Communication and Community Development.